Neoextractivism, or the birth of magical realism as world literature. Issue 3 (4th March 2021) - Terian, Andrei
ABSTRACT: In recent years, literary criticism has shown increased interest towards the manner in which fiction depicts (neo)extractivism as a set of practices whereby large quantities of natural resources are exploited for export. However, scholars have overlooked the manifestation of this phenomenon in areas and epochs other than post-1945 Latin America. Based on a close reading of two Romanian interwar novels – Cezar Petrescu's Pământ și cer and Mihail Sadoveanu's Nopțile de Sânziene – this article aims to demonstrate that extractive fictions played a decisive role in the emergence of magical realism as a narrative mode whereby the peripheries have left a distinctive mark on the configuration of world literature. My argument follows three consecutive steps: first, I explore how the two novels represent neoextractivism as a mechanism for the destruction of the biocoenosis and the othering of natives; then, I show that the magical, mythical, and supernatural distinguish themselves in the two works as the only instruments able to stop capitalist commodification; lastly, I show that the particular mode of representation the two novels deploy (which I label 'proto-magical realism') turns them into the missing link, on a transnational scale, between interwar social and regional fictions and early postwar magical realist works.